2018
DOI: 10.1051/e3sconf/20183303026
|View full text |Cite
|
Sign up to set email alerts
|

Use of formwork systems in high-rise construction

Abstract: Erection of high quality buildings and structures within a reasonable time frame is the crucial factor for the competitiveness of any construction organization. The main material used in high-rise construction is insitu reinforced concrete. The technology of its use is directly related to the use of formwork systems. Formwork systems and formwork technologies basically determine the speed of construction and labor intensity of concreting operations. Therefore, it is also possible to achieve the goal of reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These factors should be considered and if it becomes a problem, it should be addressed immediately without delay, because a delay can increase the cost of the process of construction. According to the study of Kurakova (2018), the factor of time and the erection of these buildings within a reasonable amount of time, while still upholding structural integrity and high quality is valuable for the competitive advantage of any construction institution. In correlation with this statement, the utilization of formwork systems and technologies can dictate the course and speed of construction of a high-quality building.…”
Section: Traditional Formwork Systemmentioning
confidence: 99%
“…These factors should be considered and if it becomes a problem, it should be addressed immediately without delay, because a delay can increase the cost of the process of construction. According to the study of Kurakova (2018), the factor of time and the erection of these buildings within a reasonable amount of time, while still upholding structural integrity and high quality is valuable for the competitive advantage of any construction institution. In correlation with this statement, the utilization of formwork systems and technologies can dictate the course and speed of construction of a high-quality building.…”
Section: Traditional Formwork Systemmentioning
confidence: 99%
“…Conventional formwork is made from wooden planks or multiplex and wooden beams. The formwork parts are assembled and installed at the project location (in situ) and done using manual/straightforward tools [10], [11]. This formwork is generally only used for 2-3 jobs, considering that the components can still be used for the following process [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, this type of formwork is not environmentally friendly, generates construction waste, and depletes wood resources [10]- [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs related to formwork are usually high, and studies have shown that the formwork can constitute up to 40–60% of the overall cost of a concrete structure [ 13 , 14 ]. Therefore, overestimating the lateral pressure can lead to additional and unnecessary expenses [ 15 , 16 , 17 , 18 ]. The design of the formwork is governed by the amount of lateral pressure exerted while casting.…”
Section: Introductionmentioning
confidence: 99%